Trunk muscle profile in elite tennis players with and without low back pain - Grosdent, S.; Demoulin, C.; Souchet, M.; Tomasella, M.; Crielaard, J. M.; Vanderthommen, M. (The Journal of Sports Medicine and Physical Fitness, 2016)
AIM: The aim of this study was to compare tennis players with and without low back pain (LBP) and healthy sedentary participants regarding the trunk muscle strength and flexibility.